STRATEGI KOMUNIKASI KANDIDAT PADA DEBAT PILKADA PAPUA BARAT 2024: ANALISIS ISI HUBUNGAN ANTARA FUNGSI WACANA (FUNCTION) DAN UCAPAN KEBIJAKAN (POLICY) - Mulantara, Muhammadafi; Adi Wibowo, Kunto; Fuady, Ikhsan; Rahmawan, Detta (LPPM Stikosa - AWS, 2025)
This study investigates the relationship between discourse functions (acclaim, attack, and defense) and policy content (past deeds and future plans) in the West Papua Governor and Vice Governor Election debate in 2024. This study focuses on the only candidate pair (Paslon 1) who participated in the debate, thus providing a different environment to study communication strategies in a non-competitive debate context. Content analysis was conducted through a combination of quantitative and qualitative techniques. 287 speech units were coded based on discourse function categories. The results showed that the acclaim function dominated at 94.24%, with 68.88% of the statements used to convey future plans. Since there was no debate opponent, there was only 0.58% attack function and 5.19% defense function, indicating a low confrontational strategy. A significant relationship between discourse function and policy content was found through the Chi-Square test (χ2 = 35.229; p < 0.001). However, the predictive value for 50% of the cells was less than 5. These results suggest that Paslon 1's communication strategy was affirmative and prospective, emphasizing self-image and future vision rather than defending or attacking. This study not only supports the political communication theory of strategic self-presentation, but also contributes to research on local political rhetoric in Indonesia, especially in the context of elections that lack significant competition. The results also emphasize how important debates are as a way to shape image and legitimacy, even without having a direct opponent.